Chikungunya: Diagnostic, Treatment and Challenge in Indonesia - Ali Ramzi (Jurnal Biologi Tropis, 2023)
Chikungunya based on the literature is classified as one of the many diseases that become a differential diagnosis of acute undifferentiated fever. Finally, patients with this condition are treated with empirical therapy so that often the management does not meet the standards / undertreatment. In an effort to reduce morbidity and improve the quality of care with limited modalities, history taking and physical examination as well as effective risk factor analysis are necessary in the current situation in Indonesia. Therefore, the authors raise this topic to help improve diagnostic acuity and the importance of the role of laboratory modalities in the diagnosis of chikungunya in Indonesia. Google Scholar by using the search keywords "Chikungunya" and "In Indonesia" with a time span of 2013-2023. Through a search that has been carried out using these 2 keywords, we get 10,300 publications. Based on the inclusion and exclusion results, 30 publications were obtained that could be used in compiling our literature review. Indonesia is an archipelago and is one of the countries in the world with a tropical climate, so it is certainly an ideal place for various tropical infectious diseases such as chikungunya. Although Indonesia has suppressed chikungunya incidence, Indonesia still facing some problem on diagnostic and case reporting system. This situation effect the performance of incidence validity and quality of treatment.  Chikungunya virus infection in Indonesia still requires diagnostic development efforts to anticipate future outbreaks.